The potential role of the eGFR in differentiating between true and pseudohyperkalaemia. (November 2020) - Morris, Thomas G; Lamba, Sushmita; Fitzgerald, Thomas; Roulston, Gary; Johnstone, Helen; Mirzazadeh, Mehdi
Background: Differentiating between true and pseudohyperkalaemia is essential for patient management. The common causes of pseudohyperkalaemia include haemolysis, blood cell dyscrasias and EDTA contamination. One approach to differentiate between them is by checking the renal function, as it is believed that true hyperkalaemia is rare with normal function. This is logical, but there is limited published evidence to support it. The aim of this study was to investigate the potential role of the estimated glomerular filtration rate in differentiating true from pseudohyperkalaemia. Methods: GP serum potassium results >6.0 mmol/L from 1 January 2017 to 31 December 2017, with a repeat within seven days, were included. Entries were retrospectively classified as true or pseudohyperkalaemia based on the potassium reference change value and reference interval. If the initial sample had a full blood count, it was classified as normal/abnormal to remove blood cell dyscrasias. Different estimated glomerular filtration rate cut-points were used to determine the potential in differentiating true from pseudohyperkalaemia. Results: A total of 272 patients were included with potassium results >6.0 mmol/L, with 145 classified as pseudohyperkalaemia. At an estimated glomerular filtration rate of 90 ml/min/1.73 m 2, the negative predictive value was 81% (95% CI: 67–90%); this increased to 86% (95% CI: 66–95%) by removing patients with abnormal full blood counts. When only patients with an initial potassium ≥6.5 mmol/L were included (regardless of full blood count), at an estimated glomerular filtration rate of 90 ml/min/1.73 m 2, the negative predictive value was 100%. Lower negative predictive values were seen with decreasing estimated glomerular filtration rate cut-points. Conclusion: Normal renal function was not associated with true hyperkalaemia, making the estimated glomerular filtration rate a useful tool in predicting true from pseudohyperkalaemia, especially for potassium results ≥6.5 mmol/L.